Exploitation of Unconventional CD8 T-Cell Responses Induced by Engineered Cytomegaloviruses for the Development of an HIV-1 Vaccine - Joseph Bruton; Tomáš Hanke (Vaccines)
After four decades of intensive research, traditional vaccination strategies for HIV-1 remain ineffective due to HIV-1′s extraordinary genetic diversity and complex immune evasion mechanisms. Cytomegaloviruses (CMV) have emerged as a novel type of vaccine vector with unique advantages due to CMV persistence and immunogenicity. Rhesus macaques vaccinated with molecular clone 68-1 of RhCMV (RhCMV68-1) engineered to express simian immunodeficiency virus (SIV) immunogens elicited an unconventional major histocompatibility complex class Ib allele E (MHC-E)-restricted CD8+ T-cell response, which consistently protected over half of the animals against a highly pathogenic SIV challenge. The RhCMV68-1.SIV-induced responses mediated a post-infection replication arrest of the challenge virus and eventually cleared it from the body. These observations in rhesus macaques opened a possibility that MHC-E-restricted CD8+ T-cells could achieve similar control of HIV-1 in humans. The potentially game-changing advantage of the human CMV (HCMV)-based vaccines is that they would induce protective CD8+ T-cells persisting at the sites of entry that would be insensitive to HIV-1 evasion. In the RhCMV68-1-protected rhesus macaques, MHC-E molecules and their peptide cargo utilise complex regulatory mechanisms and unique transport patterns, and researchers study these to guide human vaccine development. However, CMVs are highly species-adapted viruses and it is yet to be shown whether the success of RhCMV68-1 can be translated into an HCMV ortholog for humans. Despite some safety concerns regarding using HCMV as a vaccine vector in humans, there is a vision of immune programming of HCMV to induce pathogen-tailored CD8+ T-cells effective against HIV-1 and other life-threatening diseases.